Negative vaccine sentiments on South African social media platforms before the COVID-19 pandemic: a mixed methods study - Matsangaise, Michelle M.; Burnett, Rosemary J.; Ismail, Zeenat; Meyer, Johanna C. (Frontiers in Health Services, 2025)
IntroductionDuring the pre-pandemic era, negative vaccine sentiments did not feature in South African publications reporting on infant vaccination uptake. In contrast, vaccine hesitancy is an established driver of suboptimal COVID-19 vaccine uptake in South Africa, suggesting that the COVID-19 pandemic increased vaccine hesitancy in South Africa. This study used data from a social media tracking project to investigate vaccine sentiment expressed on South African social media platforms in the pre-pandemic era.MethodsThis mixed-methods study analysed South African social media [Twitter (now X); online news forums; microblogs] posts mentioning vaccine-related words from 1 December 2016–31 May 2017. Content analysis was used to assign vaccine sentiment, and thereafter a step-wise thematic content analysis of negative sentiment posts was conducted using NVivo12®.ResultsOf 10,997 posts about human vaccines, 16.2% expressed negative vaccine sentiments. Specific vaccines were discussed in 35.9% of posts, with human papillomavirus (HPV) vaccines attracting the most negative sentiments (31.9% of all negative posts). The majority of negative posts included links to articles emanating from other countries, predominantly the USA. Five themes were identified: Vaccine safety; autism; vaccine effectiveness; conspiracy theories; and philosophical/religious objections.DiscussionRelatively high levels of pre-existing negative sentiments toward vaccines were expressed in the pre-pandemic era, with HPV vaccines attracting the most negative comments. These results provide a baseline for comparison to post-pandemic social media studies and may prove useful for measuring the impact in South Africa of global policies introduced to limit the spread of vaccine mis- and disinformation.